Setting performance standards for regulation of water services: Benchmarking Latin American utilities - Ferro, Gustavo Adolfo (2011)
The aim of this study is to estimate both stochastic and mathematical programming efficiency cost frontiers for the Latin American water sector, by means of econometric and Data Envelopment Analysis techniques, using the ADERASA database. ADERASA is the Latin American association for water regulators, which has made a systematic job of data collection, among other initiatives. This study fills a gap in the understanding of relative efficiency in the Latin American water sector, using a consistent database. First, we present a survey of the empirical literature related to cost and production frontiers in the water and sanitation sector. Second, once alternative specifications were chosen, models have been estimated and environmental variables included in an exploratory way. The coefficients have the expected signs and plausible values. Some consistency between methodologies is found. This paper yields two results. The better knowledge of the underlying cost (or production) model is a first step to using benchmarking as a regulatory tool. The policy implications are relatively straightforward. With benchmarking technology it is possible to coordinate the action of different regulators, each with their own asymmetry of information. The key is setting indicative standards which constitute the basis of further discussion.